2013
DOI: 10.1111/jhn.12156
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine levels in breast milk are associated with mothers' dietary intake and are higher in preterm than full‐term human milk and formulas

Abstract: Dietary intake of polyamines has an impact on the content in breast milk. The difference between human milk after preterm and term delivery might be considered when using donor human milk for preterm infants. The corresponding formulas had lower contents. Further studies are important for determining the relationship between tissue growth and maturation and optimal intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
(97 reference statements)
5
24
0
Order By: Relevance
“…The major polyamines in breast milk are spermidine and spermine and their contents differ considerably, with coefficients of variation >68 and 53%, respectively. Spermine values are generally higher, except in two studies by the same author, in which higher values are reported for spermidine (11, 25). As indicated in Table 1, the breast milk analyzed in different studies corresponds to different phases of lactation, which could contribute to the high variability observed.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…The major polyamines in breast milk are spermidine and spermine and their contents differ considerably, with coefficients of variation >68 and 53%, respectively. Spermine values are generally higher, except in two studies by the same author, in which higher values are reported for spermidine (11, 25). As indicated in Table 1, the breast milk analyzed in different studies corresponds to different phases of lactation, which could contribute to the high variability observed.…”
Section: Introductionmentioning
confidence: 80%
“…It is known that during rapid cell growth, particularly in the neonatal stage, the need for polyamines increases (4, 5, 21, 23, 24). Requirements are also higher after surgery or during periods of wound-healing and aging (2, 23, 25).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scant information that is available relates only to PAs, but indicates human milk to contain substantial amounts of spermidine and spermine, and lower concentrations of putrescine [7]. PA concentrations are influenced by a number of factors including the mother’s age, her genetic background, ethnicity, nutritional status, diet, how long she has been lactating, and whether her child was born at term or was premature [8,9,10]. In infants, putrescine, spermidine and spermine are essential in cell growth and proliferation, particularly in the gut [11,12].…”
Section: Introductionmentioning
confidence: 99%